Oral Health-Related Quality of Life (OHRQoL) in Elderly Patients with and without Alzheimer's Disease - An Evaluative Study - Khan, Ambar; Untoo, Rafia; Patthi, Basavaraj; Singla, Ashish; Kumari, Monika; Rajeev, Ananthalekshmy (Indian journal of dental research, 2024)
Abstract Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterised by the loss of intellectual functions. The disorder is usually seen after the age of 60 years, and these elderly patients tend to experience a progressive decline in their cognitive and behavioural abilities. Aim: The present study was carried out to assess the oral health-related quality of life (OHRQoL) in elderly patients suffering from AD as compared to subjects without the disease. Materials and Method: One hundred elderly subjects with AD and 150 subjects without AD were included in the study. The subjective assessment of OHRQoL was done using the General Oral Health Assessment Index (GOHAI). Demographic and oral characteristics were assessed for dentition status with the Decayed, Missing and Filled Teeth (DMFT) index, Oral Hygiene Index (OHI), prosthesis use, xerostomia and presence of oral pathologies. Results: GOHAI values were found to be statistically higher (P = 0.0003) in the subjects with AD. The subjects with AD were found to have a higher DMFT (mean difference = 4.11), Oral Hygiene Index (OHI) scores (mean difference = 1.54), xerostomia (P = 0.0128) and number of oral pathologies. However, the educational level (P = 0.2603) and number of natural teeth (P = 0.0006) were found to be lower in the group with AD. Conclusion: The present study reported that the elderly subjects suffering from AD had poorer OHRQoL than those without the disease. There is a need to comprehensively evaluate the oral health conditions of elderly patients with AD and actively provide management to improve their OHRQoL.